The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s13005-016-0116-y
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of Er,Cr:YSGG laser supported periodontal therapy on the reduction of peridodontal disease related oral malodor: a randomized clinical study

Abstract: BackgroundThis study aims to evaluate the efficacy of Er,Cr:YSGG laser assisted periodontal therapy on the reduction of oral malodor and periodontal disease.MethodsSixty patients with chronic periodontitis were included in the study and allocated into two groups each containing 30 patients. The study was planned in a double blind fashion. Conventional periodontal therapy was performed in group 1 and conventional periodontal therapy was performed in association with Er,Cr:YSGG application in group 2. Periodonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 35 publications
0
33
0
1
Order By: Relevance
“…A review of the eight previously published human clinical studies using the ERL in the treatment of chronic periodontal disease 10,11,13,14,[39][40][41][42] revealed only one used a surgical control. 11 Most of these studies compared the use of the laser to SRP 13,14,[39][40][41][42] while one did not have a control. 10 The majority of studies used the ERL as an adjunct to SRP while two studies used only the laser as the test therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the eight previously published human clinical studies using the ERL in the treatment of chronic periodontal disease 10,11,13,14,[39][40][41][42] revealed only one used a surgical control. 11 Most of these studies compared the use of the laser to SRP 13,14,[39][40][41][42] while one did not have a control. 10 The majority of studies used the ERL as an adjunct to SRP while two studies used only the laser as the test therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the 10 articles evaluating the adjunctive use of laser are summarized in Table 2 (Dereci, Hatipoglu, Sindel, Tozoglu, & Üstün, 2016;Dilsiz, Canakci, & Aydin, 2013;Eltas & Orbak, 2012a;Euzebio Alves et al, 2013;Hatipoglu et al, 2017;Kamma, Vasdekis, & Romanos, 2009;Kelbauskiene, Baseviciene, Goharkhay, Moritz, & Machiulskiene, 2011;Matarese, Ramaglia, Cicciu, Cordasco, & Isola, 2017;Rotundo et al, 2010;Üstün, Hatipoglu, Daltaban, Felek, & Firat, 2018).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Smokers were reported in 3 articles (Eltas & Orbak, 2012a;Kamma et al, 2009;Rotundo et al, 2010); smokers were excluded in 6 articles (Dilsiz et al, 2013;Euzebio Alves et al, 2013;Hatipoglu et al, 2017;Kelbauskiene et al, 2011;Matarese et al, 2017;Üstün et al, 2018). Two articles reported on patients diagnosed with aggressive periodontitis (Kamma et al, 2009;Matarese et al, 2017), 7 articles on patients diagnosed with chronic periodontitis (Dereci et al, 2016;Dilsiz et al, 2013;Eltas & Orbak, 2012a;Euzebio Alves et al, 2013;Hatipoglu et al, 2017;Rotundo et al, 2010;Üstün et al, 2018), and periodontal diagnosis was not reported in 1 article (Kelbauskiene et al, 2011).…”
Section: Study Samplesmentioning
confidence: 99%
“…To date, few studies have evaluated the effects of tongue cleaning on oral malodor, although tongue debris is a major source of VSC generation. Periodontal treatments have been used along with antimicrobial mouthwash and/or tongue cleaning in most previous studies, and improvement of periodontal conditions has been reported to contribute to reduction of oral malodor (Dereci, Hatipoğlu, Sindel, Tozoğlu, & Üstün, ; Quirynen et al, ; Ren, Zhang, et al, ). The conventional scaling and root‐planing therapy used as a control treatment in those studies also led to significant reduction of oral malodor (Dereci et al, ; Ren, Zhang, et al, ).…”
Section: Inhibition Of Oral Malodormentioning
confidence: 99%